Comparative transcriptome analysis provides insights into molecular pathway and genes associated with head-type formation and phenotypic divergence in Chinese cabbage - Meng, Chuan; Liu, Xiaodong; Wu, Fang; Ma, Lei; Wang, Yuhai; Mu, Jingui; Wang, Mingqiu (Frontiers in Genetics, 2023)
Background: The heading type of Chinese cabbage is a significant commercial trait with high economic value. At present, researches on the phenotypic divergence and formation mechanism of heading type is limited. Results: Through comparative-transcriptome analysis, the formation and phenotypic divergence mechanism of the leafy head of diploid overlapping type cabbage, diploid outward-curling type cabbage, tetraploid overlapping type cabbage and tetraploid outward-curling type cabbage were systematically and comprehensively investigated, and phenotypic specific genes of four varieties were revealed. The phenotype-specific differentially expressed genes (DEGs) were considered crucial for its heading type through WGCNA analysis. Some transcription factors have been predicted as significant genes for phenotypic divergence, including the members of bHLH, AP2/ERF-ERF, WRKY, MYB, NAC, and C2CH2 families. Phytohormone-related genes including abscisic acid/ auxin hormone may play an important role in phenotypic divergence of head type in cabbage. Conclusion: The comparative-transcriptome analysis supports a role for phytohormone-related genes and some transcription factors in heading type formation and divergence for four cultivars. These findings increase our understanding of the molecular basis for pattern formation and divergence of the leafy head in Chinese cabbage and will contribute to develop more desirable leafy head patterns.